Virtual Reality Technology for Maintenance Training - Numfu, Manoch; Riel, Andreas; Noel, Frederic (Applied Science and Engineering Progress, 2020)
This paper is part of a bigger research project that aims at establishing an integrated VR environment for preparing, evaluating, and executing maintenance training in virtual environments. In order to apply the virtual reality technology to maintenance task training, this paper presents a Virtual Reality for Training in Maintenance Task (VR-TMT) platform using the simulation of the process of a gearbox disassembly and assembly as an example. The system setup and configuration are presented in detail, as well as the analysis of the experience, perception level and side effects of using VR devices. The results show that the user experience and perception levels on provided by the VR-TMT platform are on a good level. In addition to that, the VR-TMT system is easy to use, understand and flexible for transport. Users can therefore profit from the VR-TMT platform to train anywhere and anytime according to their needs. The majority of the experimental users experienced only few side effects, in particular both physical and visual tiredness. However, the experiment confirmed that the immersive experience of VR-supported maintenance task training outweighs the reported side effects.